Correction: Colorimetric Detection of Plasmodium vivax in Urine Using MSP10 Oligonucleotides and Gold Nanoparticles. - Yossef Alnasser; Cusi Ferradas; Taryn Clark; Maritza Calderon; Alejandro Gurbillon; Dionicia Gamboa; Uri S McKakpo; Isabella A Quakyi; Kwabena M Bosompem; David J Sullivan; Joseph M Vinetz; Robert H Gilman (Public Library of Science (PLoS), 2016)
[This corrects the article DOI: 10.1371/journal.pntd.0005029.].